Metabolomic analysis of vascular cognitive impairment due to hepatocellular carcinoma - Zhu, Dan; Zhu, Yamei; Liu, Lin; He, Xiaoxue; Fu, Shizhong (Frontiers in Neurology, 2023)
Screening for metabolically relevant differentially expressed genes (DEGs) shared by liver hepatocellular carcinoma (LIHC) and vascular cognitive impairment (VCI) to explore the possible mechanisms of LIHC-induced VCI. Based on metabolomic and gene expression data for LIHC and VCI, 14 genes were identified as being associated with changes in LIHC metabolites, and 71 genes were associated with changes in VCI metabolites. According to the Cancer Genome Atlas (TCGA) database, 882 LIHC-associated DEGs were identified and 343 VCI-associated DEGs were identified. Multi-omics analysis was used to screen 360 DEGs associated with LIHC metabolism and 63 DEGs associated with VCI metabolism. Eight genes were found at the intersection of these two gene sets: NNMT, PHGDH, NR1I2, CYP2J2, PON1, APOC2, CCL2, and SOCS3. The LIHC metabolomics prognostic model was constructed and proved to have a good prognostic effect. Following principal component analyses (PCA), functional enrichment analyses, immune function analyses, and TMB analyses, these eight DEGs were identified as possibly affecting LIHC-induced VCI and the immune microenvironment. As well as gene expression and gene set enrichment analyses (GSEA), a potential drug screen was conducted to investigate the possible mechanisms involved in LIHC-induced VCI. Finally, the drug screening revealed the potential clinical efficacy of A-443654, A-770041, AP-24534, BI-2536, BMS-509744, CGP-60474, and CGP-082996. Through the immune microenvironment, LIHC-associated metabolic DEGs may influence the development of VCI in LIHC patients.